Cell membrane fatty acid changes and desaturase expression of Saccharomyces bayanus exposed to high pressure homogenization in relation to the supplementation of exogenous unsaturated fatty acids - Serrazanetti, Diana I.; Patrignani, Francesca; Russo, Alessandra; Vannini, Lucia; Siroli, Lorenzo; Gardini, Fausto; Lanciotti, Rosalba (Frontiers in Microbiology, 2015)
Aims: The aim of this work was to study the responses of Saccharomyces bayanus cells exposed to sub-lethal high-pressure homogenization (HPH) and determine whether the plasmatic membrane can sense HPH in the presence, or absence, of exogenous unsaturated fatty acids (UFAs) in the growth medium. Methods and Results: HPH damaged and caused the collapse of cell walls and membranes of a portion of cells; however, HPH did not significantly affect S. bayanus cell viability (less than 0.3 Log CFU ml-1). HPH strongly affected the membrane fatty acid composition by increasing the percentage of total UFA when compared with saturated fatty acids. The gene expression showed that the transcription of OLE1, ERG3 and ERG11 increased after HPH. The presence of exogenous UFA abolished HPH-induced effects on the OLE1 and ERG3 genes, increased the percentage of membrane lipids and decreased the expression of OLE1 and ERG3 within 30 min of treatment. Conclusions: The results suggest a key role for UFA in the microbial cell response to sub-lethal stress. In addition, these data provide insight into the molecular basis of the response of S. bayanus to this innovative technology. Significance and Impact of the Study: Elucidation of the mechanism of action for sub-lethal HPH will enable the utilization of this technology to modulate the starter performance at the industrial scale.